Studi Satuan Biaya Pendidikan Sekolah Dasar di Jakarta - Ngadirin -- (Jurnal Pendidikan dan Kebudayaan, 2011)
The aim of this research is to examine the government policy in financing basic education in the frame of compulsory education which focuses on the educational policy for primary school. This includes an evaluation of all regulations related to financing education and calculation on finding the student unit cost at primary level through a survey to provide a reference for the government in allocating budget for education. The result of research shows that there are some inconsistencies in the regulations related to financing education. This includes the implementation policy on financing basic education in the frame of compulsory basic education. It is found that the education unit cost for primary school level is IDR1,767,000 per student per year. It is much higher than the current budget allocated. These findings seem to be important for all parties as a feedback and reflection for the government policy including reviewing some regulations to avoid inconsistency. ABSTRAKPenelitian ini bertujuan untuk menganalisis kebijakan pemerintah dalam bidang pembiayaan pendidikan dasar yang merupakan wajib belajar bagi setiap warga negara, dengan fokus pada pembiayaan sekolah dasar. Analisis yang dilakukan termasuk menghitung biaya satuan pendidikan untuk sekolah dasar. Hasil analisis menunjukkan bahwa terdapat beberapa ketidakkonsistenan peraturan yang berkaitan dengan pembiayaan pendidikan, termasuk kebijakan dan pelaksanaan wajib belahar pendidikan dasar. Satuan biaya pendidikan untuk sekolah dasar adalah sebesar Rp1.767.000,00 per siswa per tahun yang jauh lebih besar dari alokasi satuan biaya yang diterapkan saat ini. Hasil penelitian ini sangat penting untuk diperhatikan oleh berbagai pihak sebagai masukan bagi penyusunan kebijakan publik, terutama melalui peninjauan kembali beberapa peraturan untuk menjaga konsistensi antarkebijakan.